Peran Ekoteologi dalam Pendidikan Islam: Belajar Menjaga Alam sebagai Amanah Tuhan - Vina Mafaza; Abdul Khobir; Farah Dilah Zahra; Mohammad Ja’far Firdaus (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The global ecological crisis has shifted from being merely a technical issue to a moral-spiritual crisis rooted in an anthropocentric view. This study analyzes the role of eco-theology in Islamic education as the foundation for shaping environmental awareness from a divine perspective. Using qualitative methods with an in-depth literature review approach, this study examines the integration of the values of tawhid, khalifah, and amanah in the framework of the Islamic education curriculum. The findings reveal that Islamic eco-theology offers a transformative paradigm through theological reconstruction that positions nature conservation as a manifestation of worship and religious responsibility. Its implementation through innovative learning strategies such as project-based learning in the “Green Qur'anic School” model and contextual approaches has proven effective in shaping the ecological character of students. The implications of this research encourage the development of a holistic Islamic education model that systematically integrates ecological values through an integrated curriculum, practical habits, and character assessment, thereby producing a generation of Muslims who consistently practice environmental sustainability as a manifestation of divine trust in their daily lives.